Advancing early onset colorectal cancer research: research advocacy, health disparities, and scientific imperatives - Dwyer, Andrea J.; Rathod, Aniruddha; King, Carli; Vuik, F. E. R.; Gallagher, Phuong; Davis, Anjee; Lander, Eric M.; Perea, Jose (Frontiers in Oncology, 2024)
Early onset colorectal cancer (EOCRC) emerged as the fourth foremost contributor to cancer-related mortality among both genders in the late 1990s. Presently, EOCRC (<50) ranks as the leading cause of cancer mortality in men and the second leading cause in women within the United States 1 . Similar trends are now also evident globally, particularly in developed countries 2 . Furthermore, there is strong evidence confirming that health disparities persist in the diagnosis and treatment of EOCRC, with signs indicating that these gaps may worsen in specific cases 3 . These alarming trends highlight the critical need for research to inform evidence-based interventions to reduce the burden of EOCRC globally.Fight Colorectal Cancer (Fight CRC) is the leading patient advocacy group in the United States providing information on colon and rectal cancer research, prevention, treatment, and policy. It is the opinion of Fight CRC that an international, coordinated effort with the medical, research, scientific, advocacy, industry and funding community is needed to advance impactful research. Fight CRC, in partnership with José Perea, MD, PhD, of the Institute of Biomedical Research of Salamanca (IBSAL) in Spain, and partners, are working together to address this global phenomenon and are presenting a multi-faceted research approach to move the field forward.